Internet Addiction in the Web of Science Database: A Review of the Literature with Scientific Mapping - Moreno-Guerrero, Antonio-José (Int J Environ Res Public Health, 2020)
Information and communication technologies (ICT) is a major element of today’s society with great potential that can offer both advantages and disadvantages. Addiction to the Internet and social networks is a growing problem in all age groups. Education is the context in which to work and train in the correct use of these media. The objective of the study focuses on knowing the scientific production and the performance of the concepts “addiction” and “internet” (ADIN). A bibliometric methodology complemented with the scientific mapping technique was followed. Different processes related to the quantification, analysis, evaluation, and estimation of scientific documents were carried out. The literature was analyzed by specific programs such as SciMAT, Analyze Results, and Creation Citation Report. The unit of analysis was specified in 5644 scientific publications extracted from Web of Science (WoS), belonging to the period of years between 1996 and 2019. The results showed that the evolution in the study of the addiction to the Internet is constant and continuous, with articles in English being the most used means to present the information on the part of the investigators. In addition, the subject of study was based on time, given that the coincidence of key words between the periods analyzed was high. In conclusion, the importance of promoting healthy living habits that include responsible use of the Internet are discussed.